Model Reference Adaptive Control of a DC Motor Speed with Encoder using Hardware in the Loop - Aqsal Mufhaddhal, Muhammad; Susanto, Erwin; Ridho Rosa, Muhammad (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2024)
This study aims to design speed control of a DC motor with an encoder using the Model Reference Adaptive Control (MRAC) via hardware in the loop (HIL) system. Although conventional control such as a PID control is still found in many dc motor control applications today, but they have limitations in adaptiveness from any uncertainties and noises. Therefore, this paper proposes a more adaptive control technique. Model Reference Adaptive Control which forces the real system to follow the behavior of the reference model system even though there is uncertainty in the system dynamics.  This research includes the design of a hardware system on a loop consisting of a DC motor plant, MRAC controller, and control display. In addition, experiments were also carried out to test the performance control with sinusoidal reference signals and signal reference steps. The test results show that the MRAC control successfully follows the reference signal with low Root Mean Squared Error (RMSE) values. In conclusion, this study succeeded in designing a control on a DC encoder motor using the Model Reference Adaptive Control on the system hardware in a loop and yields satisfactory results in experimental testing